Role of Curcuma longae Rhizoma in medical applications: research challenges and opportunities - Zhang, Peng; Liu, Hong; Yu, Yuan; Peng, Shiyang; Zhu, Shaomi (Frontiers in Pharmacology, 2024)
Curcuma longae Rhizoma, commonly known as turmeric, is extensively utilized not only in Traditional Chinese Medicine (TCM) but also across various traditional medicine systems worldwide. It is renowned for its effectiveness in removing blood stasis, promoting blood circulation, and relieving pain. The primary bioactive metabolites of Curcuma longae Rhizoma—curcumin, β-elemene, curcumol, and curdione—have been extensively studied for their pharmacological benefits. These include anti-tumor properties, cardiovascular and cerebrovascular protection, immune regulation, liver protection, and their roles as analgesics, anti-inflammatories, antivirals, antibacterials, hypoglycemics, and antioxidants. This review critically examines the extensive body of research regarding the mechanisms of action of Curcuma longae Rhizoma, which engages multiple molecular targets and signaling pathways such as NF-κB, MAPKs, and PI3K/AKT. The core objective of this review is to assess how the main active metabolites of turmeric interact with these molecular systems to achieve therapeutic outcomes in various clinical settings. Furthermore, we discuss the challenges related to the bioavailability of these metabolites and explore potential methods to enhance their therapeutic effects. By doing so, this review aims to provide fresh insights into the optimization of Curcuma longae Rhizoma for broader clinical applications.